The CARL Library Impact Framework: A Logic Model Approach To Impact Assessment For Research Libraries - Robertson, Mark; Gottschalk, Tania; Wheeler, Justine (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2024)
In December 2021, the Canadian Association of Research Libraries (CARL) released the CARL Library Impact Framework (CLIF). While library impact has been a topic of discussion for many years, the CLIF offers a new contribution to the dialogue on demonstrating research libraries’ impact. The concept of impact pathways was borrowed from the Federation for the Humanities and Social Sciences report entitled Approaches to Assessing Impacts in the Humanities and Social Sciences. To realize the impact pathways concept, the CLIF has adapted a logic model framework. This approach provides users of the CLIF a way to represent a more complete arc of research libraries’ influence, systematically and visually. By design, the CLIF encourages the use of assessment techniques and tools beyond the quantitative data collection and descriptive statistics often used by research libraries. This paper provides an overview of the CLIF including its genesis, intent, structure, and possibilities for its application.